The impact of workplace support components on the mental health and burnout of UK-based healthcare professionals: Insights from the CoPE-HCP cohort study - George Collett; Alaa Emad; Ajay K. Gupta (Clinical Medicine)
Study objective: To evaluate the influence of the perceived level of workplace support and its individual components in improving mental health and reducing burnout among healthcare professionals (HCPs). Design: In a cohort of 400 HCPs followed up since July 2020, a follow-up survey was done online (August 2023) containing detailed questionnaires regarding workplace support and mental health. Participants: 400 UK-based HCPs. Main outcome measure(s): The level of individual workplace support components (perceived manager’s concern for staff welfare, transparent communication, adequate staffing/safety, visible and approachable leadership, and collegial/peer support) were assessed using self-rating scales. Depression (PHQ-9), anxiety (GAD-7), insomnia (ISI), mental wellbeing (SWEMWBS) and burnout (emotional exhaustion, aMBI-EE; and depersonalisation, aMBI-DP) were assessed using validated tools. Results: Compared with feeling unsupported, feeling supported was associated with a reduced risk of probable depression, insomnia, low wellbeing and burnout, and was associated with an increased perceived level of all individual support components. An increase in the perceived level of collegial/peer support was associated with reduced depression, anxiety, insomnia and burnout, and increased wellbeing scores (all p-values <0.01). An increase in the perceived level of managerial understanding of staff welfare was associated with reduced burnout (emotional exhaustion) among HCPs (p<0.05). There was also evidence that varying levels of visible and approachable leadership may impact on depression, anxiety and insomnia (p<0.05). Conclusions: Adverse mental health and burnout among HCPs may be mitigated by good quality workplace support, specifically by fostering collegial/peer support among staff and ensuring that managers show genuine understanding for staff welfare and are visible and approachable in their leadership. These findings may guide the allocation of workplace support resources for HCPs.